Analysis of Performance and Emission Characteristics of a Homogeneous Charge Compression Ignition (HCCI) Engine. (2016) - Hussaini, Syed Yaser; Lahane, Subhash; Patil, N.G.
Abstract: In internal combustion engines, soot-NOx paradox is extremely challenging issue, which remains to be resolved. Homogeneous charge compression ignition (HCCI) is a new combustion concept that gives benefits such as diesel like efficiency and resolves the problem of high level of NOx and PM simultaneously. It gives very high rate of heat release which cannot be easily controlled. The present work deals with development of HCCI engine and performance and emission investigations of combustion on petrol fuelled single cylinder engine. Homogeneous mixture preparation is the most critical part of the HCCI combustion concept. To achieve homogeneous mixture of fuel and air, petrol was used. The mixture was introduced in combustion chamber through carburetor, controlled by throttling, the intake manifold specially fabricated for the engine under consideration. Experiments were performed at variable speed to observe behavior of HCCI combustion. The engine's load carrying capacity was controlled by regulating the air and fuel flow. It was observed that engine could run smoothly at lean air fuel mixture but knocking was noticed at rich air fuel mixture. Compared with base engine, NOx and smoke opacity were observed to be reduced by 78% and 100% respectively with modified engine (HCCI) as compared to base engine.